FGF21 Protects Against Hypoxia Injury Through Inducing HSP72 in Cerebral Microvascular Endothelial Cells - Wang, Hao-Wei; Jiang, Xin; Zhang, Yu; Wang, Jian; Xie, Jian; Wang, Yong-Qiang; Li, Yong-Hua (Frontiers in Pharmacology, 2019)
Background: Fibroblast growth factor 21 (FGF21), a member of a family of atypical FGFs, functions as cytokine to control endocrinology and metabolism. Recently, the roles of FGF21 in cardio-cerebral-vascular diseases have been gradually uncovered. In the present study, we investigated the effect of FGF21 on bEnd.3 cerebral microvascular endothelial cells (CMECs) upon hypoxia stress. Methods and Results: CMECs were cultured in the condition of 1% O2 for 8 h to induce hypoxia stimuli. For FGF21 treatment, recombinant FGF21 (50 nM) was added into the culture medium. Various biomedical assays were used to evaluate the hypoxia-induced injury in CMECs. Under normoxia condition, FGF21 had no obvious effect on cell viability and did not cause any cytotoxicity on CMECs. Under hypoxia condition, FGF21 significantly attenuated the hypoxia-induced injury, evidenced by the influences of FGF21 on CMEC viability and LDH release. TUNEL staining assay and immunoblotting of caspase-3 showed that FGF21 reduced hypoxia-induced apoptosis in CMECs. Mechanistically, FGF21 treatment compromised the hypoxia-induced changes of reactive oxygen species, malondialdehyde, total antioxidant activity, and total superoxide dismutase levels. FGF21 administration decreased hypoxia-induced matrix metalloprotein 3 and matrix metalloprotein 2/9 activity in CMECs. Activities of cyclooxygenase-2 and NF-κB-p65, two pro-inflammatory factors, were also upregulated by hypoxia but suppressed by FGF21. At last, we found that FGF21 increased heat shock protein family A member 1A (HSP72) mRNA and protein expression. Blockade of HSP72 by a pharmacological inhibitor VER155008 or specific siRNA-mediated knockdown abrogated the protection of FGF21 against hypoxia in CMECs. Conclusion: These data demonstrate that FGF21 protects against hypoxia stress-induced injury in CMECs by inducing HSP72 expression, suggesting a therapeutic value of FGF21 in hypoxia-related brain diseases such as ischemic stroke and acute mountain sickness.